If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + 8 = 1 Reorder the terms: 8 + 7y = 1 Solving 8 + 7y = 1 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 7y = 1 + -8 Combine like terms: 8 + -8 = 0 0 + 7y = 1 + -8 7y = 1 + -8 Combine like terms: 1 + -8 = -7 7y = -7 Divide each side by '7'. y = -1 Simplifying y = -1
| 4m=12 | | 0.65x+.05(8-x)=.10(76) | | -28p-6(3-6p)=6(p-4)-2 | | 400x-100(30-x)=0 | | 8x^2-7x+4=-3x+2 | | 3x+41-6x=2-9x+3 | | t+23=15 | | 48(b+12)=63+56b | | x+.40=4 | | =3(2y+4)7-30 | | 2x-3(1-3x)=10 | | 4t^3-27t^2+60t-45=0 | | 10u-98=3u | | -9(v+2)+3v+7=8v+7 | | 10-98=3u | | -5z=11-6z | | 4x^2-9x-33=0 | | x^2+3x+8=-4x-2 | | 7-4x=3l | | 105=(2x-11) | | M+18=36 | | x^2-x+4=6 | | 7x(6+9x)-2x(8+5x)= | | h=300+3.5h | | -5=c/4/3 | | -3d+7=1-5d | | 4t^3-9t^2+60t-45=0 | | (x+8)+4=x+(8+4) | | 6x-5=3x+10 | | -3x-47=73-8x | | -4x^2+2=-3x | | 9(x+7)-(8x+4)=-9 |